2020
DOI: 10.3390/ijerph17197252
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve Compliance with Protective Health Measures during the COVID-19 Outbreak: Testing a Moderated Mediation Model and Machine Learning Algorithms

Abstract: In the wake of the sudden spread of COVID-19, a large amount of the Italian population practiced incongruous behaviors with the protective health measures. The present study aimed at examining psychological and psychosocial variables that could predict behavioral compliance. An online survey was administered from 18–22 March 2020 to 2766 participants. Paired sample t-tests were run to compare efficacy perception with behavioral compliance. Mediation and moderated mediation models were constructed to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
97
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 67 publications
(88 reference statements)
7
97
1
3
Order By: Relevance
“…This is consistent with other studies showing that, for both adolescents and adults, the main motivations for social distancing include social responsibility and desire to protect others ([ 31 ], Coroiu, 2020 #6246, Oosterhoff, 2020 #6214). These results are further confirmed by another study conducted among Italian adults that showed that in the context of COVID-19, civic attitudes, including the feeling of involvement in the community, have an impact on adherence to preventive measures [ 32 ]. Therefore, promoting altruism and community attachment could be a potential strategy to enhance AYAs’ uptake of current preventive measures, and could also encourage vaccination once it will be available.…”
Section: Discussionsupporting
confidence: 67%
“…This is consistent with other studies showing that, for both adolescents and adults, the main motivations for social distancing include social responsibility and desire to protect others ([ 31 ], Coroiu, 2020 #6246, Oosterhoff, 2020 #6214). These results are further confirmed by another study conducted among Italian adults that showed that in the context of COVID-19, civic attitudes, including the feeling of involvement in the community, have an impact on adherence to preventive measures [ 32 ]. Therefore, promoting altruism and community attachment could be a potential strategy to enhance AYAs’ uptake of current preventive measures, and could also encourage vaccination once it will be available.…”
Section: Discussionsupporting
confidence: 67%
“…For instance, taking advantage of the more widespread use of Web technologies, experts might utilize online assessments to evaluate depression, stress, personality features, and coping style, especially in younger Italians. Such a screening process could reach a high number of people at risk for mental disease in a short span of time, and thereby prevent the spread of psychopathologies in the coming years and promote compliance with the government-recommended health measures [38].…”
Section: Resultsmentioning
confidence: 99%
“…Interventions, such as promoting public compliance with government health recommendations to control the spread of a virus should also be included. Such research could focus on the public perceptions and efficacy of a range of interventions ( Roma et al, 2020 ). Meanwhile, physical characteristics such as green space should be taken into account in a future study since previous studies have indicated that the percentage of green space.…”
Section: Discussionmentioning
confidence: 99%